Pricing and Causality Among Selected Fats and Oils - Mohd. Arshad, Fatimah; Lubis, A. Rahman; A. Ghaffar, Roslan (Universiti Putra Malaysia Press, 1993)
This paper studies the nature of price relationships among selected prices of five fats and oils (palm oil, soybean, coconut, fish oils and tallow) to provide empirical evidence as to the competitive structure of the fats and oils market. The fats and oils market is highly competitive and price is shown to be simultaneously discovered by the market with minimum lags and distortions. Statistical causality models developed by Granger, Sims and Haugh-Pierce were used to examine this hypothesis. Inferences are made as to the applicability of the models in understanding the nature of the market.